Sustaining key skills in the UK military aircraft industry - Bassford, Matt (Rand Corporation monograph series., 2010)
"In December 2005, the Ministry of Defence (MOD) published its first Defence Industrial Strategy, containing a specific reference to the military fixed wing aircraft sector and a requirement to retain domestic design and engineering capabilities, as well as other skills, to perform through-life activities. In 2009, the House of Commons Defence Committee urged the MOD to "set out what assessment it has made of the health of the UK defence industry and, in particular, those parts of the defence industry where the MOD wishes to retain industrial capability in the UK." The research reported in this monograph was commissioned by the MOD's Fixed Wing Sector Strategy Board to assist the MOD in its development of a strategy and sustainment plan for the military fixed wing sector. The RAND study was conducted between August and December 2009 and focused on the current health and future sustainment of key skills in the UK fixed wing military industrial base. This monograph describes the qualitative and quantitative methodologies that the RAND team followed and summarises its findings and recommendations."--Provided by publisher.